Internalisasi Nilai-Nilai Pendidikan Akhlak Dalam Tradisi Lokal "Silek Pangian" Nagari Tabiang Tinggi (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Islamic education plays a crucial role in character formation, but the younger generation is facing a moral crisis, making the local tradition of “Silek Pangian” in Nagari Tabiang Tinggi relevant as a medium for internalizing values. This study aims to describe the internalization process, identify values, and analyze supporting and inhibiting factors of moral education in “Silek Pangian”. Using a qualitative descriptive case study approach, the study involved 12 informants (students, teachers, traditional leaders) in Nagari Tabiang Tinggi. Data were collected through in-depth interviews, participant observation, and document analysis, with instruments in the form of interview guides and observation sheets. Data analysis followed the interactive model of Miles and Huberman, and data validity was guaranteed through triangulation. The results showed that the process of internalizing moral values occurred through the delivery of advice, habituation of attitudes, and deepening of inner study, consistent with the cognitive, affective, and psychomotor dimensions. Four core values were identified: Imat (wise), Caromat (careful), Hadomat (respectful), and Lamo Maso (persistent), which collectively shape the character of wisdom, simplicity, courage, and justice. Internalization is supported by students' beliefs and traditional ceremonies, but hampered by the influence of the modern environment and gadgets. Essentially, Silek Pangian functions as a character education system based on local wisdom that effectively shapes individuals with leadership qualities, courage, responsibility, and justice.
Keywords: Islamic Education; Silek Pangian; Internalization of Moral Values; Internalization; Character